Economic Efficiency and Profitability of Islamic Bank - Mohamad Akbar Noor, Mohamad Noor (2011)
This thesis investigates various performance measurements of 78 Islamic banks during the period of 1992 to 2009 in term of bank efficiency, bank efficiency determinants, profitability and relationship between bank efficiency determinants and profitability. We compute the bank efficiency of Islamic banks by using the non-parametric Data Envelopment Analysis (DEA) method. Our findings show that during the period of study, pure technical efficiency outweighs scale efficiency in Islamic banking countries. Then we examine the Determinants of Islamic Banks’ Efficiency on the second stage based on DEA output in the first stage, a multivariate analysis based on the Tobit model, exploring the proximate sources of (in) efficiency under the multivariate framework and relating the findings to bank specific characteristics. We also incorporate macroeconomic variables as control variables to test the effect of external factors on Islamic bank efficiency determinants and profitability. The findings of bank efficiency determinants reinforces DEA findings with technical efficiency has a positive relationship and statistical significance at 1% level on all 10 models. We then test the profitability of Islamic banks; the profit efficiency estimated the Islamic bank by using the least square method of Fixed Effects Model (FEM) to control bank-specific effects. The empirical results show novel finding that Islamic banks profitability does not have an impact during Asia and Global Financial Crisis. While for Middle East and North Africa (MENA) and Asian also negative with Asian being statistically significant at 10% level implying that Islamic banks operated at Asian are less profitable compared to Islamic bank at MENA. For country income level, the findings stated that Islamic banks operating from MEDIUM Income countries have negative relationship with profitability and statistical significance at 1% level while HIGH income countries have positive relationship and statistical significance at 10% level. This is interesting since MEDIUM & HIGH income countries have different result findings between one and another. We then test the relationship between bank efficiency determinants and profitability. Favourable economic conditions and inclination towards Islamic banking may have fuelled higher demands for Islamic banking products and services that reduce default loan probabilities, thus resulting in profitability. We also find positive correlation between bank profitability and technical efficiency levels, indicating that the more efficient banks tend to be more profitable.